Hubungan Motivasi Belajar, Keterampilan Komunikasi, dan Dukungan Orang Tua terhadap Kesiapan Kerja Generasi Muda di SMAK Kasih Anugrah Kelas XII (Jurnal Manajemen Kreatif dan Inovasi, 2026)
The high unemployment rate in Indonesia highlights the importance of enhancing work readiness among young people from an early educational stage. Work readiness is influenced by several factors, including learning motivation, communication skills, and parental support. This study aims to examine the relationship between learning motivation, communication skills, and parental support with work readiness among twelfth-grade students at SMAK Kasih Anugrah. This research employed a quantitative approach with a cross-sectional design. The population consisted of all 30 twelfth-grade students, and a saturated sampling technique was applied. Data were collected using structured questionnaires and analyzed through univariate and bivariate analysis using the Chi-Square test. The results indicate a significant relationship between learning motivation and work readiness (p-value = 0.021), communication skills and work readiness (p-value = 0.014), and parental support and work readiness (p-value = 0.005). These findings suggest that learning motivation, communication skills, and parental support play a crucial role in improving students’ readiness to enter the workforce. The results of this study are expected to provide practical implications for schools and parents in strengthening students’ preparation for the world of work